Airing the Ungeographic: Anacostia Unmapped and Black Geographies of Gentrification in Washington, DC - Nimoh, Suzanne (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
In 2019, Washington, DC was the fastest gentrifying city in the United States (Helmuth 2019). Once known as a Chocolate City, tens of thousands of Black residents have been displaced in recent decades. Anacostia, a predominantly Black neighborhood east of the Anacostia River in Washington, DC, is one of the areas intensely impacted by gentrification. This article examines the use of storytelling as resistance to gentrification in Anacostia, through the radio show Anacostia Unmapped. Through oral history analysis, I demonstrate how Black residents of Anacostia use storytelling to create alternative maps of their communities, countering dominant maps that erase them. I argue through radio, residents share and create Black geographic knowledge, despite narratives of gentrified modernity assigning them as ungeographic. I analyze three vignettes from Anacostia Unmapped to demonstrate how residents unmap cartographic exclusion and housing displacement, and remap geographies of care and intimacy. My analysis of Anacostia Unmapped shows how the medium of radio produces space at varying scales, forefronting residents' sense of place outside of the modern visual and cultural aesthetics of modernity, and narrating Black relationships to the city at intimate scales. I extend scholarship on Black soundscapes and gentrification, arguing the stories aired on Anacostia Unmapped are sonic maps of retention, resistance, and care. My work also brings an examination of racial power to Euro-centric scholarship on radio geographies.